The RNA-binding protein RBM3 is required for cell proliferation and protects against serum deprivation-induced cell death - Wellmann, Sven; Truss, Matthias; Bruder, Elisabeth; Tornillo, Luigi; Zelmer, Andrea; Seeger, Karl; Bührer, Christoph (Pediatric research, 2010)
Hypoxia and other adverse conditions are commonly encountered by rapidly growing cells. The RNA-binding protein RBM3 (RNA-binding motif protein 3), which is transcriptionally induced by low temperature and hypoxia, has recently been implicated in survival of colon cancer cells by mechanisms involving cyclooxygenase-2 (COX-2) signaling. Immunohistochemically, we found strong RBM3 expression in a variety of malignant and proliferating tissues but low expression in resting and terminally differentiated cells. RBM3 expression in fibroblasts and human embryonal kidney (HEK293) cells subjected to serum deprivation or contact inhibition closely paralleled proliferation rates, assessed by real-time RT-PCR and immunoblotting. siRNA-mediated RBM3 knockdown reduced cell viability and finally led to cell death, which did not involve caspase-3-mediated apoptosis, cell cycle arrest, or COX-2 regulation. In contrast, RBM3 over-expression rescued cells from death under serum starvation. This was associated with increased translation rates, as measured by C serine and H phenylalanine incorporation. Together, RBM3 is a critical factor providing cellular survival advantages in an adverse microenvironment presumably by restoring translation efficacy.